KERALA'S ECONOMIC DEVELOPMENT : EMERGING ISSUES AND CHALLENGES - B A PRAKASH; JERRY ALWIN (LONDON SAGE, 2018)
Focusing on current economic problems, this book provides an in-depth analysis of the major development issues and challenges faced by the state. Kerala's development experience has attracted worldwide attention due to its paradoxical development: attaining higher quality of life people on the one hand and continuation of the backward productive sectors on the other. The state's economy remained backward in many respects and relied heavily on the remittance of Keralite emigrants. The implementation of liberalisation and globalisation policies since 1991 radically altered the growth process and Kerala achieved higher rates of investment and growth and greater technological change. These policies, however, have not only provided enormous opportunities, but also new challenges. This book examines the state's economic growth as well as the issues that have accompanied the policy changes
Keywords: ECONOMIC DEVELPOMENT - KERALA